Enlightening Education on Quranic Perspective - Ahmad zain Sarnoto (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This article is to reveal that education is not only dealing with issues of intelligence and thinking, but it is also fully responsible for the development of a student's character. Due to the said reason, it is important to explore such research considering that the mental situation of this nation is clearly correlated with the spirit of national education which has been value-free. Our educational philosophy is indeed intellectual, but our learning strategy is no longer concerned with the mental, moral, and developmental aspects of enlightening thinking skills. Al-Qur'an for Muslims is not a mere religious scripture, but it is also indeed to be an enlightening guide to find some basic principles of education which can then inspire in developing a qualified education. This study uses the Qur'anic literature method as well as descriptive and qualitative research with a library research approach by analyzing Qur’anic verses. This article analyzes the signs of al-Qur'an as the basic framework for building an enlightening education.